Towards gender equality through women empowerment project based on herbal products in Catur Kintamani, Bali - Putu Chris Susanto; Ni Made Diana Erfiani; I Putu Darmawijaya; Putu Indah Lestari (Community Empowerment, 2022)
The use and subsequent development of herbal products has been on the rise in Indonesia. Catur village, in the mountainous district of Kintamani, the heart of Bali Island, is a region rich in herbal plants. However, the villagers have yet to realize the great potential that they have, and simultaneously they are in search of a unique proposition for their rural tourism development. The team from Universitas Dhyana Pura set out a four-year project for empowering the women of Catur village to be actively involved in their local economic development through education, cultivation, production, and marketing of locally sourced herbal products. This article discusses the second cycle of this project, carried out in 2019-2021. Joint efforts by the project team and the target group have yielded several economically viable herbal products (output), while the women reported that the feel more empowered to be involved in their families’ and village’s efforts towards economic welfare, and that there is a multiplier effect from this project on the education and uses of herbal products strengthening the establishment of Catur as “herbal village.”